Traffic impacts of dynamic bus lanes: a simulation experiment of real-world bus operations - Johan Olstam; Carl Henrik Häll; Kinjal Bhattacharyya; Rihanna Gebrehiwot (European Transport Research Review)
Abstract As buses often share space with other vehicles, their travel time and reliability are affected by the flow of traffic. This can be mitigated by prioritization measures as bus streets or bus lanes, but such measures are not always possible due to limited space or too large impact on other traffic. An alternative is dynamic bus lanes, which only are reserved for buses when needed. The aim of this article is to explore the feasibility of dynamic bus lanes through a case study of a main arterial towards the city centre of a low/medium sized city with multiple bus lines arriving at different intersections along the main arterial. This is investigated by setting up and calibrating a microscopic traffic simulation model for a real world case. The simulation model is used to study impacts of dynamic bus lanes compared to two cases: current operations of mixed traffic (no bus lane) as baseline, and dedicated bus lane. The simulation results demonstrate that dynamic bus lanes can contribute to keeping a good punctuality even at higher traffic demands, this due to decreased travel time variability. However, the total travel time for all travellers (independent of mode) increase (even if buses are assumed to be full).